Distribution of aetiological types of stroke among the diabetic adults admitted with stroke in a referral hospital: an observational study - Mahapatra, Umakanta; Ganai, Saikot; Pulai, Debabrata; Saha, Dipan; Swaika, Bikash Chandra (International Journal of Basic & Clinical Pharmacology, 2021)
Background: Stroke is one of the most devastating disorders worldwide, in terms of morbidity and mortality. Association of comorbid conditions increase severity and chances of unfavourable outcome in stroke patients. Diabetes is one of the vital comorbidity risk factors reported to be associated with occurrence, poor outcome in stroke patients. An increased incidence of stroke has been reported in advanced age among diabetic patients. The aim of this study was to determine the relative distribution of aetiological types of stroke among the stroke patients having diabetes. Methods: All adults (18-65) admitted in medicine indoor of Midnapore medical college and hospital with a provisional diagnosis of stroke having random blood glucose level ≥200 mg/dl and/or h/o diabetes were enrolled and screened for different etiological factors e.g., hypertension, dyslipidemia. Age group and gender wise distribution pattern were also obtained. Results: A total 384 subjects were included in the study. Hypertension was found to be most common (75%) comorbid condition among participants, followed by dyslipidemia (56%). 77.9% of subjects presented with random glucose level of >200 mg/dl. Conclusions: stroke of either types is very much prevalent among diabetes. Uncontrolled diabetes along with hypertension and dyslipidemia increases the chance many times. Early detection and prompt therapeutic intervention may reduce the mortality rate overall.